2012
DOI: 10.1016/j.biomaterials.2012.06.066
|View full text |Cite
|
Sign up to set email alerts
|

The responses to surface wettability gradients induced by chitosan nanofilms on microtextured titanium mediated by specific integrin receptors

Abstract: Microtexture and chemistry of implant surfaces are important variables for modulating cellular responses. Surface chemistry and wettability are connected directly. While each of these surface properties can influence cell response, it is difficult to decouple their specific contributions. To address this problem, the aims of this study were to develop a surface wettability gradient with a specific chemistry without altering micron scale roughness and to investigate the role of surface wettability on osteoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 39 publications
2
67
0
Order By: Relevance
“…However, it is usually difficult to evaluate the specific contribution of wettability because wettability is strongly affected by the surface roughness and chemistry. Recent attempts to modify wettability without changing the surface microstructure and chemistry have revealed that hydrophilic surfaces modulated the expression profile of integrin subunits and enhanced osteogenic cell differentiation 50,51) . The hypothetical mechanism of the effects of hydrophilic surfaces on cell attachment and subsequent reactions is that the hydrophilicity influences the protein absorption to the material surface and prevents the entrapment of air bubbles within the surface architecture, which could interfere with protein absorption and materialcell interaction 49) .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is usually difficult to evaluate the specific contribution of wettability because wettability is strongly affected by the surface roughness and chemistry. Recent attempts to modify wettability without changing the surface microstructure and chemistry have revealed that hydrophilic surfaces modulated the expression profile of integrin subunits and enhanced osteogenic cell differentiation 50,51) . The hypothetical mechanism of the effects of hydrophilic surfaces on cell attachment and subsequent reactions is that the hydrophilicity influences the protein absorption to the material surface and prevents the entrapment of air bubbles within the surface architecture, which could interfere with protein absorption and materialcell interaction 49) .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies reveal that metal ions released from the electrochemical corrosion, even detected at sublethal doses, can affect the osteoblasts and osteoclasts differentiation 27,29,28 . Metal implants can degrade through corrosion and wear process, nevertheless, synthetic hardware as polyethylene degrades only through wear process 28 .…”
Section: 25mentioning
confidence: 99%
“…According , the selected experimental times were 1 and 2 weeks since previous works showed that in vivo experiments for up to 8 weeks exhibited significant modifications at implantations on this periods 28 .…”
Section: In Vivo Implantationmentioning
confidence: 99%
See 2 more Smart Citations